ULF Wave Modeling, Effects, and Applications: Accomplishments, Recent Advances, and Future - Hartinger, Michael D.; Takahashi, Kazue; Drozdov, Alexander Y.; Shi, Xueling; Usanova, Maria E.; Kress , Brian (Frontiers in Astronomy and Space Sciences, 2022)
Ultra Low Frequency (ULF) waves play important roles in magnetosphere-ionosphere coupling, ring current and radiation belt dynamics, and modulation of higher frequency wave modes and energetic particle precipitation. The "ULF wave modeling, effects, and applications" (UMEA) focus group - part of the Geospace Environment Modeling effort from 2016-2021 - sought to improve understanding of the physics of ULF waves and their specification in geospace models. Through a series of in person and virtual meetings the UMEA focus group brought modelers and experimentalists together to compare ULF wave outputs in different models, plan observation campaigns focused on ULF waves, discuss recent advances in ULF wave research, and identify unresolved ULF wave science questions. This article summarizes major discussion points and accomplishments in the UMEA focus group over the last 6 years, recent advances and their connection to Richard Thorne and Peter Gary's significant contributions to ULF wave research, and the future of ULF wave research.